UNEVEN DEVELOPMENT OF THE WORLD ECONOMY: FROM KRUCMANTO LENIN. (1st April 2010) - Unknown
Abstract : The ongoing world economic crisis has revealed the fundamental weight shift of the global economy from the Western world to East Asia. In my understanding, this shift is due to the "uneven development" that Lenin defined in Imperialism, in which he also proved the validity of this historical law. In his theory, this kind of uneven development is the basic condition of the conflicts among capitalist countries. In this article, first, we review Krugman's model of "uneven development" between two countries, namely, South and North, because he said his model expresses Lenin's theory of "uneven development." Second, we show that he has misunderstood Lenin's theory and that Lenin's theory is more realistic than Krugman's. As we know, Paul Krugman won a Nobel Prize in 2008. In this sense, this article also reveals a critical problem of the Nobel Prize in economics.